Shear stress affects the architecture and cohesion of Chlorella vulgaris biofilms - A. Fanesi (Nature Portfolio, 2021)
Abstract The architecture of microalgae biofilms has been poorly investigated, in particular with respect to shear stress, which is a crucial factor in biofilm-based reactor design and operation. To investigate how microalgae biofilms respond to different hydrodynamic regimes, the architecture and cohesion of Chlorella vulgaris biofilms were studied in flow-cells at three shear stress: 1.0, 6.5 and 11.0 mPa. Biofilm physical properties and architecture dynamics were monitored using a set of microscopic techniques such as, fluorescence recovery after photobleaching (FRAP) and particle tracking. At low shear, biofilms cohesion was heterogeneous resulting in a strong basal (close to the substrate) layer and in more loose superficial ones. Higher shear (11.0 mPa) significantly increased the cohesion of the biofilms allowing them to grow thicker and to produce more biomass, likely due to a biological response to resist the shear stress. Interestingly, an acclimation strategy seemed also to occur which allowed the biofilms to preserve their growth rate at the different hydrodynamic regimes. Our results are in accordance with those previously reported for bacteria biofilms, revealing some general physical/mechanical rules that govern microalgae life on substrates. These results may bring new insights about how to improve productivity and stability of microalgae biofilm-based systems.